La reivindicació identitària en els narradors del Realisme Compromès de la postguerra - Vicent Simbor Roig (Catalonia)
The paper reviews the realistic and engagé movements that cover the European postwar years. And then it studies the parallel Catalan movement focusing on the problem of identity assertion in the narrative. In many of our narrators of this realism of complaint (Concepció G. Maluquer, Estanislau Torres, Víctor Mora and Joaquim Carbó) national commitment accompanyies social and political commitment. It is a peculiar trait that distinguishes our movement and gives the physiognomy of its own.